Protein Kinase C-α Activity Is Required for Respiratory Syncytial Virus Fusion to Human Bronchial Epithelial Cells - San-Juan-Vergara, Homero (American Society for Microbiology, 2004)
Respiratory syncytial virus (RSV) infection activates protein kinase C (PKC), but the precise PKC isoform(s) involved and its role(s) remain to be elucidated. On the basis of the activation kinetics of different signaling pathways and the effect of various PKC inhibitors, it was reasoned that PKC activation is important in the early stages of RSV infection, especially RSV fusion and/or replication. Herein, the role of PKC-α during the early stages of RSV infection in normal human bronchial epithelial cells is determined. The results show that the blocking of PKC-α activation by classical inhibitors, pseudosubstrate peptides, or the overexpression of dominant-negative mutants of PKC-α in these cells leads to significantly decreased RSV infection. RSV induces phosphorylation, activation, and cytoplasm-to-membrane translocation of PKC-α. Also, PKC-α colocalizes with virus particles and is required for RSV fusion to the cell membrane. Thus, PKC-α could provide a new pharmacological target for controlling RSV infection.